ANALISIS KELAYAKAN USAHA - laneva, apredo; Loice, Romy; Hartono, Robby (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study has four main objectives, namely: (1) Determine the feasisibilty of the Padang Restaurant business in Kota Baru from the legal aspect, (2) Determine the feasibility of the Padang Restaurant business in Kota Baru from the market and marketing aspect, (3) Determine the feasibility of the Padang Restaurant business in Kota Baru from the technical and operational aspect, (4) Determine the feasibility of the Padang Restaurant business in Kota Baru from the financial aspect. The Kota Baru Restaurant is a business engaged in the culinary sector, by offering products in the form of Padang dishes which are located on Jalan Jenderal A.Yani in the city of Baturaja. The Kota Baru Restaurant was established in 1972 and closed in 2019 due to bankruptcy. In 2023, the Kota Baru Restaurant owner plans to reopen the Kota Baru Restaurant business. So with that in order to reopen the Kota Baru Restaurant business, a business feasibility analysis is needed so that bankruptcy does not occur for the second time. In terms of the legality aspect, the Kota Baru Restaurant is said to be feasible because the Kota Baru Restaurant can fulfill the existing requirements, namely licensing to open a business in Baturaja City and open a business in the culinary field. In the market and marketing aspects it is said to be feasible because it has a market as evidenced by collecting traffic data using the work sampling method so that a fairly large market segment is obtained, namely road users in front of restaurants with a lifestyle of eating out and an interest in buying food outside. From the technical and operational aspects, the Kota Baru Restaurant is said to be feasible because it meets the specifications, which include production and sales locations, there are demand estimates and production estimates, there are process flows, adequate production and sales facilities and there is also a workforce that assists operational activities. From the financial aspect it is said to be feasible because the Kota Baru Restaurant has met the financial feasibility specifications seen from the Net present value (NPV), amounting to IDR 643,623,829,13, Discounted Payback Period for 1.27 years and Internal Rate of Return (IRR) of 64% for the most likely scenario. Based on the four aspects that have been analyzed, it can be said that the Kota Baru restaurant deserves to be reopened.